Adsorption energetics of azobenzenes on noble metal surfaces - Schulze, Michael; Bronner, Christopher; Tegeder, Petra (Journal of physics. Condensed matter, 2014)
Temperature-programmed desorption measurements have been applied to investigate the binding energies of four systems, namely the photochromic molecular compounds azobenzene and tetra-tert-butyl-azobenzene (TBA) adsorbed on the Au(1 1 1) and Ag(1 1 1) surfaces, respectively. The binding energy is a measure of the interaction strength between substrate and adsorbate. It therefore provides a suitable means for an investigation of the decoupling strategy pursued by adding the tert-butyl spacer groups and choosing the more inert gold substrate, which leads to TBA/Au(1 1 1), the only photoisomerizable system out of the four. Ironically, we find TBA/Au(1 1 1) to be the most strongly bound. The binding of TBA to Au(1 1 1) is almost 0.4 eV stronger than to Ag(1 1 1). On the other hand, azobenzene binds approximately equally strongly to both surfaces. These findings are consistent with and provide support for the recently proposed hybridization between the HOMO of TBA and the Au(1 1 1) d-band needed for the hole attachment which induces the isomerization.